JURIDICAL IMPLICATIONS OF THE UTILIZATION OF COASTAL BOUNDARIES BY TOURISM ENTREPRENEURS IN TANJUNG BIAS WEST LOMBOK - Sahlan, Sahlan; Erwin, Yulias; Septyanun, Nurjannah (Universitas Labuhanbatu, 2025)
This study aims to find out and analyse the use and impact of beach areas that are not in accordance with laws and regulations as tourism support. The methods used in this study are normative and empirical legal methods with legislative, conceptual, case, and sociological approaches. The results of this research show that the act of privatization and the use of beach areas in West Lombok, especially in Tanjung Bias Beach, where culinary entrepreneurs in the form of cafes, restaurants and hotels tend to have an impact that results in a decrease in the function of coastal boundaries, which is characterized by the narrowing and pollution of the beach. This is certainly contrary to Regional Regulation Number 11 of 2011 concerning the Regional Spatial Plan of West Lombok Regency, that the spatial pattern plan has been determined as a tourism strategic area and an economic strategic area. Keywords: Juridical implications; Coastal Borders; Utilization, Tourism